Foreign Ownership, Capital Intensity, Investment Opportunity, Tax Haven’s Affiliates and Aggressive Tax Avoidance of Foreign-owned Businesses during Pandemic - Arja Sadjiarto; Richard William Santosa; Surya Timoer (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
The purpose of this research is to observe whether or not foreign ownership, capital intensity, investment opportunity, and tax haven’s affiliates affect aggressive tax avoidance, especially during the pandemic time in the year 2020 and 2021. The research sample consists of 69 companies registered in Indonesia Stock Exchange with foreign ownership above 25%. This research utilizes multiple linear regression method by using WarpPLS. The result indicates that capital intensity and tax haven countries positively affects aggressive tax avoidance. Foreign ownership and investment opportunity does not affect aggressive tax avoidance.